2014
DOI: 10.1063/1.4901112
|View full text |Cite
|
Sign up to set email alerts
|

Role of solvation in pressure-induced helix stabilization

Abstract: In contrast to the well-known destabilization of globular proteins by high pressure, recent work has shown that pressure stabilizes the formation of isolated α-helices. However, all simulations to date have obtained a qualitatively opposite result within the experimental pressure range. We show that using a protein force field (Amber03w) parametrized in conjunction with an accurate water model (TIP4P/2005) recovers the correct pressure-dependence and an overall stability diagram for helix formation similar to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…The fraction of native structure for each residue is shown visually in Figure 4a in ∆G f −u is small and almost certainly within the statistical error in the study. [44][45][46][47][48] It is difficult to distinguish between the native and denatured ensembles using the radius 14 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37...…”
Section: Resultsmentioning
confidence: 99%
“…The fraction of native structure for each residue is shown visually in Figure 4a in ∆G f −u is small and almost certainly within the statistical error in the study. [44][45][46][47][48] It is difficult to distinguish between the native and denatured ensembles using the radius 14 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37...…”
Section: Resultsmentioning
confidence: 99%
“…S5 and Table S3). The TIP4P/2005 water model was used for its ability to capture pressure‐dependent equilibria, in conjunction with the Amber ff99SBws protein force field optimized for this water model . The simulation pressure was set to be the same as in experiment.…”
Section: Resultsmentioning
confidence: 99%
“…23 Separately, it has been reported that folding of small helical motifs can be promoted under high-pressure conditions due to preferential hydration of helical structure. [25][26][27] These evidences suggest that unfolded protein chains may not remain entirely featureless at high-pressure.…”
Section: Introductionmentioning
confidence: 98%